A Bibliometric Survey of Research Output on Wireless Charging for Electric Vehicles - Emmanuel Gbey; Richard Fiifi Turkson; Sohui Lee (World Electric Vehicle Journal, 2022)
Wireless charging modules for electric vehicles are being increasingly studied. Previous research has focused on developing more effective wireless-charging modules for electric vehicles in order to pave the way for a more sustainable urban transportation. The objectives of the study were to identify the social structure of the field by mapping of research collaborations among authors and countries, measure the influence of authors and sources, identify the interactions between different researchers and the most influential authors, sources, documents and organizations. To achieve these objectives, a bibliometric search in the SCOPUS database was conducted using a combination of keywords and Boolean operators. The initial keyword search returned 2163 documents. The documents retrieved were manually filtered for further analysis. A scientometric analysis was carried out on the remaining 1367 documents using co-authorship, co-citation, and citation analyses for a number of measurement units. The results showed that “object detection” and “shielding effectiveness” were the most current research topics. Authors who were widely cited did not generally produce a large number of papers or collaborate with other authors. Authors from China, the United States, and the United Kingdom have all co-authored published works on the topic, indicating that they have all contributed considerably to the field’s achievements. This strongly highlighted the amount of funding localized in developed countries towards such technologies. The number of international co-authored studies conducted was low. This is most significant with no research conducted in this field in the less developed world. The most cited and influential scholars were G. A. Covic, J. T. Boys, and C. C. Mi. The most influential sources were IEEE Trans. on Power Electronics and IEEE Trans. on Induction Electronics, while the most productive sources were Energies and IEEE Access. The most influential documents were those by Covic G.A. (2013a) and Covic G.A. (2013b). Finally, emerging trends in charging and energy storage in electric vehicles were also discussed.